The Effects of Taxation on the Selling of Corporate Stock and the Realization of Capital Gains - Feldstein, Martin; Slemrod, Joel; Yitzhaki, Shlomo (Quarterly Journal of Economics, 1980)
This study provides the first econometric analysis of the effect of taxation on the realization of capital gains. The analysis thus extends and complements the earlier study by Feldstein and Yitzhaki [1978] of the effect of taxation on the selling of corporate stock. The present analysis, using a large, new body of data obtained from individual tax returns, supports the earlier finding that corporate stock sales are quite sensitive to tax rates and then shows that the effect on the realization of capital gains is even stronger.